Ab initio determination of a simultaneous dual-ion charging mechanism for Ni0.25Mn0.75O2 through redox reactions of Ni2+/Ni4+ and O2−/O−. Issue 36 (1st September 2022) - Shepard, Robert; Brennan, Scott; Juran, Taylor R; Young, Joshua; Smeu, Manuel
Abstract : A novel method for computationally determining anion voltage is proposed in which one must consider full electrolyte interactions. This work reveals a simultaneous dual-ion (Na and ClO4 ) charging mechanism for Ni0.25 Mn0.75 O2 . Abstract : Over recent years, great efforts have been made to push the limits of layered transition metal oxides for secondary battery cathodes. This is particularly true for overall capacity, which has reached a terminal theoretical value for many materials. One avenue for increasing this capacity during charging is the intercalation of anions post cation deintercalation. This work investigates the charging mechanism of the P3-Na0.5 Ni0.25 Mn0.75 O2 cathode material through cation (Na) deintercalation and anion (ClO4 ) intercalation by means of density functional theory. The calculations corroborate experimental findings of increased capacity (135 mA h g −1 to 180 mA h g −1 ) through the intercalation of anions. However, this work demonstrates that a process of simultaneous cation deintercalation/anion intercalation is the primary charging mechanism, with charge compensation reactions of Ni 2+ /Ni 4+ and O 2− /O − occurring within the cathode material. To elucidate this simultaneous process, a novel method for computationally determining anion voltage in which one must consider full electrolyte interactions is proposed. Based on the results, it is believed that a simultaneous cation deintercalation/anion intercalation mechanism provides one potential avenue for the discovery of the next generation of secondary batteries.